Perspective on Terahertz Applications in Bioscience and Biotechnology - Markelz, A. G.; Mittleman, D. M. (ACS Photonics, 2022)
Within the field of terahertz science and technology, one of the most active areas of current research focuses on the intersection of terahertz measurements and methods with the world of biology and medicine. Current activities revolve around numerous diverse questions, ranging from studies of the vibrational spectra of biomolecules and macromolecular complexes to biosensing to medical diagnostics based on noninvasive imaging techniques. Unlike many other areas in which terahertz science is now making inroads, this research domain has been plagued with a number of misleading ideas, which originated at least two decades ago and continue to crop up in current literature. In the worst case, these unfortunate notions can distract from, and even obscure, fascinating and meaningful results. The purpose of this Perspective is to highlight a few of these mistaken concepts and, more importantly, to distinguish them from the many interesting works that continue to emerge from the fruitful marriage of terahertz with biology and medicine.

Anisotropic Terahertz Microscopy of Lysozyme in Different CrystalLattice Systems - McKinney, J. A.; George, D. K.; Deng, Y.; Markelz, A. G. (Biophysical Journal, 2021)
Long-range vibrational modes of proteins at terahertz (THz) frequencies havebeen associated with protein function and allosteric control. The characteriza-tion of these motions has been challenging due to energy overlap with waterabsorption and a large vibrational density of states. Recently it has been demon-strated both experimentally and theoretically that vibrational bands can be iso-lated using stationary sample anisotropic terahertz microscopy (SSTAM) fororiented samples, typically realized using protein crystals [1, 2]. In those earlymeasurements, inhibitor binding contrast was demonstrated for high symmetrytetragonal crystals. While high symmetry crystals are ideal for structural deter-minations, they can limit the types of vibrations observable in the ATM mea-surements. Here we show a survey of ATM measurements of triclinic,monoclinic and tetragonal crystals, demonstrating the unique signaturesobservable for the different symmetry groups, leading to a more completedetermination of the vibrational hot spots that may contribute to enzymatic ef-ficiency. The SSATM spectra indicate the presence of conserved vibrationalmodes near 40 cm-1 and 55 cm-1 for CEWL in triclinic, monoclinic and tetrag-onal lattice systems respectively. For CEWL in the monoclinic lattice system, aprominent band at 20cm1was consistently observed in the SSATM spectrabut not in the triclinic or tetragonal systems. The conserved bands may repre-sent vibrational modes that are unperturbed by crystal contact forces while thedifferences may be related to unique molecular orientation in different crystalsystems. 1.Niessen, K., Y. Deng, and A.G. Markelz,Near-field THz micropo-larimetry.Opt Express, 2019.27(20): p. 28036-28047. 2.Romo, T.D., A.Grossfield, and A.G. MarkelzPersistent Protein Motions in a RuggedEnergy Landscape Revealed by Normal Mode Ensemble Analysis. AcceptedJournal of Chemical Information and Modeling, 2020.

Apparatus and method for analyzing a sample - Markelz, Andrea G; Acbas, Gheorghe; Niessen, Katherine A. (USPTO, 2021)
An apparatus and method for Crystal Anisotropy Terahertz Microscopy (“CATM”) is provided. The apparatus includes an emitter configured to emit a THz pulse and a detector configured to detect the THz pulse after the pulse is transmitted through a sample disposed on a sample surface of the detector. A pulsed radiation generator generates a probe beam to interrogate the detector. The detector may include an electro-optical (“EO”) crystal configured to change in birefringence according to the THz pulse. The sample surface of the detector may have a dielectric coating which is transmissive to THz and reflective to the probe beam. The sample is disposed on the dielectric coating.

Functional-State Dependence of Picosecond Protein Dynamics - George, D. K.; Chen, J. Y.; He, Yunfen; Knab, J. R.; Markelz, A. G. (J. Phys. Chem. B, 2021)
We examine temperature-dependent picosecond dynamics of two benchmarking proteins lysozyme and cytochrome c using temperature-dependent terahertz permittivity measurements. We find that a double Arrhenius temperature dependence with activation energies E1 ∼ 0.1 kJ/mol and E2 ∼ 10 kJ/mol fits the folded and ligand-free state response. The higher activation energy is consistent with the so-called protein dynamical transition associated with beta relaxations at the solvent–protein interface. The lower activation energy is consistent with correlated structural motions. When the structure is removed by denaturing, the lower-activation-energy process is no longer present. Additionally, the lower-activation-energy process is diminished with ligand binding but not for changes in the internal oxidation state. We suggest that the lower-energy activation process is associated with collective structural motions that are no longer accessible with denaturing or binding.

Near-Field Stationary Sample Terahertz Spectroscopic Polarimetry for Biomolecular Structural Dynamics Determination - Deng, Y.; McKinney, J. A.; George, D. K.; Niessen, K. A.; Sharma, A.; Markelz, A.G. (ACS Photonics, 2021)
THz polarimetry on environmentally sensitive and microscopic samples can provide unique insight into underlying mechanisms of complex phenomena. For example, near-field THz anisotropic absorption successfully isolated protein structural vibrations which are connected to biological function. However, to determine how these vibrations impact function requires high throughput measurements of these complex systems, which is challenged by the need for near field detection, sample environmental control and full polarization variation. Stationary sample anisotropic terahertz spectroscopy (SSATS) and near-field stationary sample anisotropic terahertz microscopy (SSATM) have been proposed using synchronous control of THz and electro optic probe polarizations along an iso-response curve. Here we realize these techniques through robust control and calibration of the THz and NIR polarization states. Both methods rapidly measure the linear dichroism in the far field and near field. Validation measurements using standard birefringent sucrose single crystals found the crystal orientation can be determined by scanning the reference polarization and the synchronous pump–probe polarization settings can be optimized to eliminate artifacts. SSATM is then used to determine spectral reproducibility and dehydration effects for a series of chicken egg white lysozyme samples. Reproducible anisotropic absorbance bands are found at about 30, 44, 55, and 62 cm–1. These bands initially sharpen with slow dehydration, similar to the increase in resolution achieved in X-ray crystallographic protein structure determination. The SSATM technique confirms the reliability of anisotropic absorption characterization of protein intramolecular vibrations and opens an avenue for rapid determination of how these long-range dynamics affect biological function.

Phonon Kinetics of Fructose at the Melting Transition - A. Davie; F. Vandrevala; S. Dampf; Y. Deng; D. K. George; E. D. Sylvester; T. Korter; E. Einarsson; J. B. Benedict; A. G. Markelz (J. Phys. Chem. C, 2021)
Terahertz time domain spectroscopy (THz TDS) is used to measure the melting kinetics of fructose molecular crystals. Combining single-crystal anisotropy measurements with density functional calculations, we assign the phonon frequencies and interrogate how specific phonons behave with melting. While nearly all the low-frequency phonons continuously red-shift with heating and melting, the lowest-energy phonon polarized along the c-axis blue-shifts at the melting temperature, suggesting an initial structural change immediately before melting. We find that the kinetics follow a 3D growth model with large activation energies, consistent with previous differential scanning calorimetry (DSC) measurements. The large activation energies indicate that multiple H-bonds must break collectively for the transition. The results suggest the generality of the kinetics for molecular crystals and that THz TDS with picosecond resolution could be used to measure ultrafast kinetics.

Photo-Switching of Protein Dynamical Collectivity - M. Xu; D. George; R. Jimenez; A. Markelz (Photonics, 2021)
We examine changes in the picosecond structural dynamics with irreversible photobleaching of red fluorescent proteins (RFP) mCherry, mOrange2 and TagRFP-T. Measurements of the protein dynamical transition using terahertz time-domain spectroscopy show in all cases an increase in the turn-on temperature in the bleached state. The result is surprising given that there is little change in the protein surface, and thus, the solvent dynamics held responsible for the transition should not change. A spectral analysis of the measurements guided by quasiharmonic calculations of the protein absorbance reveals that indeed the solvent dynamical turn-on temperature is independent of the thermal stability/photostate however the protein dynamical turn-on temperature shifts to higher temperatures. This is the first demonstration of switching the protein dynamical turn-on temperature with protein functional state. The observed shift in protein dynamical turn-on temperature relative to the solvent indicates an increase in the required mobile waters necessary for the protein picosecond motions, that is, these motions are more collective. Melting-point measurements reveal that the photobleached state is more thermally stable, and structural analysis of related RFP’s shows that there is an increase in internal water channels as well as a more uniform atomic root mean squared displacement. These observations are consistent with previous suggestions that water channels form with extended light excitation providing O2 access to the chromophore and subsequent fluorescence loss. We report that these same channels increase internal coupling enhancing thermal stability and collectivity of the picosecond protein motions. The terahertz spectroscopic characterization of the protein and solvent dynamical onsets can be applied generally to measure changes in collectivity of protein motions.

Evidence of Intramolecular Structural Stabilization in Light Activated State of Orange Carotenoid Protein - McKinney, J. A.; Sharma, A.; Crossen, K.; Deng, Y.; George, D. K.; Lechno-Yossef, S.; Kerfeld, C.; Markelz, A. G. (Biophysical Journal, 2020)
Orange carotenoid protein (OCP) controls efficiency of the light harvesting antenna, the phycobilisome (PBS), in diverse cyanobacteria and prevents oxidative damage. It is the only known photoactive protein that uses a carotenoid, canthaxanthin, as its chromophore. The structure of OCP consists of two globular domains, connected by an unstructured loop, that forms a hydrophobic pocket for the carotenoid. In low light, canthaxanthin bound OCP is inactive and appears orange. Illumination by strong light results in an active state that interacts with the PBS to induce fluorescence quenching, a red appearance and conformational changes that include a 12Å shift by canthaxanthin into the N-terminal domain. Terahertz (THz) dynamical transition measurements and anisotropic terahertz microscopy are used to measure the intramolecular structural dynamics in the inactive and active states, which can be induced by photoexcitation or chaotropic salts. The measurements indicate that the active state has a decrease in structural flexibility, which may be related to enhanced interactions with the PBS.
Keywords: Biophysics

Linear dichroism infrared resonance in overdoped, underdoped, and optimally doped cuprate superconductors - Mukherjee, A.; Seo, J.; Arik, M. M.; Zhang, H.; Zhang, C. C.; Kirzhner, T.; George, D. K.; Markelz, A. G.; Armitage, N. P.; Koren, G.; Wei, J. Y. T.; Cerne, J. (Physical Review B, 2020)
By measuring the polarization changes in terahertz, infrared, and visible radiation over an extended energy range (3-2330 meV), we observe symmetry breaking in cuprate high-temperature superconductors over wide energy, doping, and temperature ranges. We measure the polarization rotation (Re[theta(F)]) and ellipticity (Im[theta(F)]) of transmitted radiation through thin films as the sample is rotated. We observe a twofold rotational symmetry in theta(F), which is associated with linear dichroism (LD) and occurs when electromagnetic radiation polarized along one direction is absorbed more strongly than radiation polarized in the perpendicular direction. Such polarization anisotropies can be generally associated with symmetry breakings. We measure the amplitude of the LD signal and study its temperature, energy, and doping dependence. The LD signal shows a resonant behavior with a peak in the few hundred meV range, which is coincident with the midinfrared optical feature that has been associated with the formation of the pseudogap state. The strongest LD signal is found in underdoped films, although it is also observed in optimally and overdoped samples. The LD signal is consistent with an electronic nematic order which is decoupled from the crystallographic axes as well as novel magnetoelectric effects.
Keywords: Materials Science; Physics

Long Range Correlated Motions of TIM and their Possible Influence on Enzyme Function - McKinney, J. A.; Deng, Y. T.; George, D. K.; Richard, J.; Markelz, A. G. (Biophysical Journal, 2020)
The alpha-beta barrel structure of triosephosphate isomerase (TIM) is possibly the most common among enzymes. In the case of TIM, structural dynamics are known to be essential to function. In particular the stabilization of the binding pocket by a phosphodianion “handle” of the substrate and the closing of catalytic site loops 6 and 7 over the substrate. Loop 6 moves by as much as 7 Angstroms with binding. Recently a mutant survey for human TIM (hsTIM) found kcat can change significantly for a single mutation distant from the catalytic site. Crystallographic measurements find no structural change with the mutation, suggesting a dynamical mechanism for the allosteric effect. Here we use Stationary Sample Anisotropic Terahertz Microscopy (SSATM) to measure the long-range intramolecular vibrations and determine if specific vibrations couple the allosteric and catalytic sites. SSATM isolated protein long-range structural vibrations based on the dominant displacement direction [1-4]. We examine if specific vibrational bands are associate with loop 6 and loop 7 flexibility.
Keywords: Biophysics

Persistent Protein Motions in a Rugged Energy Landscape Revealed by Normal Mode Ensemble Analysis - Romo, T. D.; Grossfield, A.; Markelz, A. G. (Journal of Chemical Information and Modeling, 2020)
Proteins are allosteric machines that couple motions at distinct, often distant, sites to control biological function. Low-frequency structural vibrations are a mechanism of this long-distance connection and are often used computationally to predict correlations, but experimentally identifying the vibrations associated with specific motions has proved challenging. Spectroscopy is an ideal tool to explore these excitations, but measurements have been largely unable to identify important frequency bands. The result is at odds with some previous calculations and raises the question what methods could successfully characterize protein structural vibrations. Here we show the lack of spectral structure arises in part from the variations in protein structure as the protein samples the energy landscape. However, by averaging over the energy landscape as sampled using an aggregate 18.5 mu s of all-atom molecular dynamics simulation of hen egg white lysozyme and normal-mode analyses, we find vibrations with large overlap with functional displacements are surprisingly concentrated in narrow frequency bands. These bands are not apparent in either the ensemble averaged vibrational density of states or isotropic absorption. However, in the case of the ensemble averaged anisotropic absorption, there is persistent spectral structure and overlap between this structure and the functional displacement frequency bands. We systematically lay out heuristics for calculating the spectra robustly, including the need for statistical sampling of the protein and inclusion of adequate water in the spectral calculation. The results show the congested spectrum of these complex molecules obscures important frequency bands associated with function and reveal a method to overcome this congestion by combining structurally sensitive spectroscopy with robust normal mode ensemble analysis.
Keywords: Chemistry; Computer Science; molecular-dynamics; Pharmacology & Pharmacy; photoactive yellow protein; spectroscopy; state; vibrational-modes

Is the Protein Dynamical Transition useful? - Sharma, A.; George, D. K.; Crossen, K.; McKinney, J.; Kerfeld, C.; Markelz, A. (Biophysical Journal, 2020)

Stabilization of Terahertz Vibrational Modes in Illuminated Orange Carotenoid Protein Crystals - McKinney, J.; Sharma, A.; Deng, Y.; George, D.; Lechno-Yossef, S.; Kerfeld, C.; Markelz, A. (2020 45th International Conference on Infrared, Millimeter, and Terahertz Waves (IRMMW-THz), 2020)
Orange carotenoid protein (OCP) controls efficiency of the phycobilisome (PBS), the light harvesting antenna in cyanobacteria, to prevent oxidative damage. The OCP switches from resting state to photo protective state with intense blue light illumination. Questions persist as to why OCPR interaction increases with the PBS over that with the OCPO. Here we examine the role of long-range intramolecular vibrations within OCP. Using Stationary Sample Anisotropic Terahertz Microscopy (SSATM) we measure changes in the intramolecular vibrations with photo switching. We report the first observation of switching in the intramolecular vibrations with photoexcitation. Results suggest that there is a stiffening of the molecule in the photo protective state. This increase in structural stability may enhance the interaction with the PBS change in OCP interaction with PBS. In low light, carotenoid bound OCP appears orange (OCP o ) and is inactive. Illumination by strong light converts OCP to the active, red (OCPR) state, which interacts with the PBS. A comparison of anisotropic THz microscopy measurements of dark adapted (OCP o ) and illuminated OCP crystals indicate differences in their vibrational modes that may be important for OCP-PBS interactions.

THz Transmission through Submillimeter Apertures - LaFave, T.; Lee, A.; Kao, T.-Y.; Markelz, A. (IRMMW-THz, 2020)
Terahertz near-field microspectroscopy is emerging as an essential tool for characterization of novel materials and biomolecules. It is important to ensure the near field geometry used does not introduce spectral artifacts. For example, many scanning techniques can be strongly influenced by the interaction between the scattering tip and the sample. Here we examine the spectroscopic effects of a 200 μm diameter aperture for THz near-field measurements. We use HFSS to model free-space transmission through samples with resonant absorbance as a function of sample thickness, lateral sample width, and aperture diameter. We examine the transmitted power and spectral fidelity for coupling of transmitted THz light onto a detector. These studies inform corrective post-measurement analysis algorithms and design of near-field detection systems.

Angular Distortion Removal of THz Anisotropic Dichroism Microscope - Y. Deng; K. Niessen; A. Markelz (2019 44th International Conference on Infrared, Millimeter, and Terahertz Waves, 2019)
We have developed a stationary sample THz anisotropic dichroism microscope as a powerful tool for material characterization. The key innovation is the use of an iso-response curve defined by the terahertz and detection light polarizations. Here we show that following a continuous iso-response curve introduces angular distortion in the spectrum, and this distortion can be eliminated by using a discontinuous iso-response angle pairs avoiding large gradient regions. Employing this additional constraint on the relative polarizations provides a convenient technique for rapid anisotropic terahertz spectroscopy.
Keywords: absorption; angular distortion removal; Biomedical measurement; continuous iso-response curve; detection light polarizations; discontinuous iso-response angle pairs; Distortion; light polarisation; material characterization; Microscopy; proteins; rapid anisotropic terahertz spectroscopy; relative polarizations; spectroscopy; stationary sample; terahertz spectroscopy; terahertz wave spectra; THz anisotropic dichroism microscope; vibrations

Anisotropic Terahertz Microscopy of Protein Collective Vibrations: Crystal Symmetry and Hydration Dependence - McKinney, J.; Deng, Y. T.; Sharma, A.; George, D. K.; Markelz, A. G. (2019 44th International Conference on Infrared, Millimeter, and Terahertz Waves, 2019)
A stationary sample anisotropic terahertz microscopy technique is used to characterize the intramolecular vibrations for lysozyme. Tetragonal and triclinic crystals are compared. We find excellent reproducibility within a single crystal symmetry group. Several resonant bands are present for both symmetry groups, indicating they originate with the intramolecular vibrations and not crystal lattice phonons. Bands become more pronounced and higher frequency resonant bands begin to emerge with slight dehydration.

Blue Shift of a Molecular Crystal Phonon at the Solid to Liquid Phase Transition - Davie, Alex; Vandrevala, Farah; Deng, Yanting; George, D.; Sylvester, Eric D.; Korter, T.; Einarsson, E.; Benedict, Jason B.; Markelz, Andrea (Bulletin of the American Physical Society, 2019)

Deuteration and Inhibitor Binding Dependence of Protein Collective Vibrations - Deng, Y. T.; McKinney, J.; Markelz, A. (Biophysical Journal, 2019)
Keywords: Biophysics

The Effect of Crystal Contact Forces on the Protein Global Motions - McKinney, J. A.; Deng, Y. T.; George, D.; Markelz, A. (Biophysical Journal, 2019)
Keywords: Biophysics

Near-field THz micropolarimetry - Niessen, K.; Deng, Y. T.; Markelz, A. G. (Optics Express, 2019)
We introduce a method for rapid determination of anisotropic terahertz absorption with sub micron resolution and high spectral integrity in the terahertz range. The method is ideal for microscopic and environmentally sensitive materials such as 2-D materials and protein crystals where the anisotropic absorption is critical to understanding underlying physics. We introduce the idea of using an iso-response relationship between the THz polarization and electro optic probe polarization to enable stationary sample polarization measurements covering a full 2 pi polarization dependence measurement. (C) 2019 Optical Society of America under the terms of the OSA Open Access Publishing Agreement
Keywords: binding; conductivity; dynamics; modes; Optics; polarization modulation; Terahertz; time-domain spectroscopy; wse2

Photo Switching of Protein Dynamical Collectivity - Xu, M.; George, D. K.; Jimenez, R.; Markelz, A. G. (arXiv:1906.00893, 2019)

Protein and RNA dynamical fingerprinting - Niessen, Katherine A; Xu, Mengyang; George, Deepu K; Chen, Michael C; Ferré-D’Amaré, Adrian R; Snell, Edward H; Cody, Vivian; Pace, James; Schmidt, Marius; Markelz, Andrea G (Nature communications, 2019)

Protein Intramolecular Motions with Deuteration and Inhibitor Binding Dependence - Deng, Y.; McKinney, J.; Romo, T.; Grossfield, A.; Markelz, A. G. (APS R63.003, 2019)

Spectral Assignment of Lysozyme Collective Vibrations - Deng, Y. T.; McKinney, J.; Romo, T.; Grossfield, A.; Markelz, A. (Biophysical Journal, 2019)
Global structural vibrations at terahertz (THz) frequencies have been associated with protein function and allosteric control. A chief obstacle to utilizing this control mechanism has been measurement of specific motions. Recently it was shown that while the vibrational density of states, and isotropic absorption spectra are broad and featureless, collective vibrations can be isolated based on their directionality using aligned samples (realized with protein crystals) and anisotropic THz microscopy [1]. However the assignment of resonant bands to specific structural motions was complicated by the high symmetry of the tetragonal crystals used, and the slow experimental method. To structurally map the vibrations of the chicken egg white lysozyme (CEWL) we measure anisotropic absorption of triclinic crystals using our new technique: ideal polarization varying anisotropic THz microscopy (IPV-ATM). The low symmetry triclinic crystals provide absolute protein orientation, and the near field IPV-ATM rapidly measures broadband terahertz linear dichroism of the microcrystals. All measurements were performed at room temperature under 100% humidity conditions. The unit cell parameters of triclinic lysozyme nitrate crystals, α = 28.5A°, b = 32.7A°, c = 35.1A°, α = 88.2°, β = 108.9°, γ = 111.9°, belonging to the P1 space group, were determined by X-ray diffraction before and after THz measurements. The intramolecular vibrational absorbance of the triclinic crystals has a more complex polarization dependence than the higher symmetry tetragonal crystals, as expected. While the tetragonal crystals have two strong bands at 45cm−1 and 55cm−1, the triclinic crystals have a series of narrow bands between 40 and 60cm−1 and a prominent band at 30cm−1. We compare the measured spectra to normal mode ensemble averaged calculations to assign the observed resonances, and isolating which collective motions impact the catalytic site.
Keywords: Biophysics

Stationary Sample Anisotropic THz Spectroscopy using Discretely Tunable THz Sources - LaFave, T., Jr.; George, D. K.; Markelz, A. G.; McNee, Ian; Kozlov, Vladimir; Schunemann, Peter (2019 44th International Conference on Infrared, Millimeter, and Terahertz Waves, 2019)
We demonstrate anisotropic THz spectroscopy of sucrose using newly developed compact discretely tunable THz sources for turn-key spectroscopic systems.

Tunable Compact Narrow Band THz Sources for Frequency Domain THz Anisotropic Spectroscopy - George, D. K.; LaFave, T. J.; Markelz, A. G.; McNee, I.; Tekavec, P.; Kozlov, V.; Schunemann, P. (Conference on Next-Generation Spectroscopic Technologies XII, 2019)
We demonstrate frequency domain THz anisotropy signature detection for protein crystal models using newly developed compact tunable narrow band THz sources based on Orientation Patterned Gallium Phosphide for turn-key spectroscopic systems.
Keywords: anisotropy; biomolecules; femtosecond; optical rectification; orientation patterned gallium phosphide; Terahertz; THz generation

Tunable narrow band sources for anisotropic THz spectroscopy - George, D. K.; McNee, I.; Tekavec, P.; Kozlov, V.; Schunemann, P.; Markelz, A. G. (APS S23-002, 2019)

Tunable narrowband THz generation in orientation patterned gallium phosphide for THz anisotropy identification - McNee, I.; Tekavec, P.; Kozlov, V.; Markelz, A. G.; George, D. K.; Schunemann, P. (Nonlinear Frequency Generation and Conversion: Materials and Devices Xviii, 2019)
We demonstrate tunable narrowband THz generation by optical rectification of a femtosecond pulse in Orientation Patterned Gallium Phosphide. Center frequencies of 0.9 - 3.8 THz with average power up to 15 mu W were achieved using a 1.064 mu m fiber laser for the pump laser. Biomolecular characterization for an early application of this system is also shown in this work by anisotropic spectroscopic signature detection of molecular crystals in the THz region.
Keywords: anisotropy; biomolecules; femtosecond; optical rectification; orientation patterned gallium phosphide; Terahertz; THz generation

Increase in Dynamical Collectivity and Directionality of Orange Carotenoid Protein in the Photo-Protective State - Deng, Y. T.; Luck, C. H.; Romo, T. D.; Grossfield, A. M.; Bandara, S.; Ren, Z.; Yang, X. J.; Markelz, A. G. (Biophysical Journal, 2018)
Keywords: Biophysics

Investigation of the Isotope Shift in Protein Collective Vibrations - Luck, C.; Xu, M.; Markelz, A. (APS 2018, 2018)

Measuring Protein Intramolecular Dynamics with Terahertz Light: Functional Changes and Relevance to Biology - Xu, M.; Deng, Y.; Luck, C.; Sharma, A.; Markelz, A. (APS 2018, 2018)

Rapid Terahertz Dichroism Near Field Microscopy for Biomolecular Intramolecular Vibrational Spectroscopy - Deng, Y.; Niessen, K.; Markelz, A. (APS 2018, 2018)

Terahertz Light Fingerprints Biomolecular Dynamics - Deng, Yanting; Xu, Mengyang; Niessen, Katherine A; George, Deepu Koshy; Markelz, Andrea G (CLEO: Science and Innovations, 2018)

THz Anisotropy Identification using Tunable Compact Narrow Band THz Sources - George, D. K.; Markelz, A. G.; McNee, I.; Tekavec, P.; Kozlov, V.; Schunemann, P. (2018 43rd International Conference on Infrared, Millimeter, and Terahertz Waves, 2018)
We demonstrate THz anisotropy signature determination of a protein crystal model using newly developed compact tunable narrow band THz sources for turn-key spectroscopic systems for the bio molecular community.

The 2017 terahertz science and technology roadmap - Dhillon, S. S.; Vitiello, M. S.; Linfield, E. H.; Davies, A. G.; Hoffmann, M. C.; Booske, J.; Paoloni, C.; Gensch, M.; Weightman, P.; Williams, G. P.; Castro-Camus, E.; Cumming, D. R. S.; et al. (Journal of Physics D-Applied Physics, 2017)
Science and technologies based on terahertz frequency electromagnetic radiation (100 GHz-30 THz) have developed rapidly over the last 30 years. For most of the 20th Century, terahertz radiation, then referred to as sub-millimeter wave or far-infrared radiation, was mainly utilized by astronomers and some spectroscopists. Following the development of laser based terahertz time-domain spectroscopy in the 1980s and 1990s the field of THz science and technology expanded rapidly, to the extent that it now touches many areas from fundamental science to 'real world' applications. For example THz radiation is being used to optimize materials for new solar cells, and may also be a key technology for the next generation of airport security scanners. While the field was emerging it was possible to keep track of all new developments, however now the field has grown so much that it is increasingly difficult to follow the diverse range of new discoveries and applications that are appearing. At this point in time, when the field of THz science and technology is moving from an emerging to a more established and interdisciplinary field, it is apt to present a roadmap to help identify the breadth and future directions of the field. The aim of this roadmap is to present a snapshot of the present state of THz science and technology in 2017, and provide an opinion on the challenges and opportunities that the future holds. To be able to achieve this aim, we have invited a group of international experts to write 18 sections that cover most of the key areas of THz science and technology. We hope that The 2017 Roadmap on THz science and technology will prove to be a useful resource by providing a wide ranging introduction to the capabilities of THz radiation for those outside or just entering the field as well as providing perspective and breadth for those who are well established. We also feel that this review should serve as a useful guide for government and funding agencies.
Keywords: ex-vivo; generation; metal wave-guides; near-field; performance; photoconductive emitters; Physics; quantum-cascade lasers; radiation; semiconductors; Terahertz; thz; time-domain spectroscopy

Escaping the Water Cage: Protein Intramolecular Vibrations and the Dynamical Transition - Xu, M. Y.; Niessen, K. A.; Deng, Y. T.; Michki, N. S.; Markelz, A. G. (Biophysical Journal, 2017)
Keywords: Biophysics

Global Picosecond Structural Dynamics of Orange Carotenoid Protein in Photo/Chemical Activated Signaling States - Deng, Y.; Xu, M.; Liu, H.; Blankenship, R.; Markelz, A. (APS 2017 S4.002, 2017)

Importance of Protein Vibration Directionality on Function - Niessen, Katherine A.; Xu, Mengyang; Deng, Yanting; Snell, Edward H.; Markelz, Andrea G. (Biophysical Journal, 2017)

Moving in the right direction: protein vibrations steering function - Niessen, Katherine A; Xu, Mengyang; Paciaroni, Alessandro; Orecchini, Andrea; Snell, Edward H; Markelz, Andrea G (Biophysical Journal, 2017)

Orange Carotenoid Protein Picosecond Dynamics Changes with Photo and Chemical Activation - Deng, Y. T.; Xu, M. Y.; Liu, H. J.; Blankenship, R. E.; Markelz, A. G. (Biophysical Journal, 2017)
Keywords: Biophysics

Temperature dependence of phonons in photosynthesis proteins - Xu, M.; Myles, D.; Blankenship, R.; Markelz, A. (APS 2017 S4.003, 2017)

Anisotropic Absorption Measurements Reveal Protein Dynamical Transition in Intramolecular Vibrations - Xu, M. Y.; Niessen, K.; Michki, N.; Deng, Y. T.; Snell, E.; Markelz, A. G. (2016 41st International Conference on Infrared, Millimeter, and Terahertz Waves, 2016)
Modeling has predicted that intramolecular structural vibrations enables proteins to access functionally important structural change. We show that the vibrational density of states and the isotropic absorption in the terahertz range are only weakly dependent on the protein functional state for several bench marking proteins. At the same time the direction of motions changes dramatically with functional state and with a resulting impact on the anisotropic absorption. Our anisotropic THz microscopy (ATM) measurements confirm this sensitivity. Here we apply the technique to the question of whether the protein dynamical transition (DT) is important to protein function. We find a strong anisotropic resonance at 70 cm(-1) rapidly increases in strength at temperatures above the DT. As these intramolecular vibrations enable protein structure to change conformation, the results suggest function will cease below DT for those proteins that require large scale conformational change.

Direct Measurements of the Long-Range Collective Vibrations of Photoactive Yellow Protein - Deng, Yanting; Xu, Mengyang; Niessen, Katherine A.; Schmidt, Marius; Markelz, Andrea G. (30th Anniversary Symposium of The Protein Society, 2016)
Long-range collective vibrations are thought to be crucial to protein functions. In the case of photoactive protein family, modeling suggests the intramolecular vibrations provide an efficient means of energy relaxation[1], feedback for enhancement of chromophore vibrations that promote structural transitions[2] and can assist in charge energy transfer[3]. As a paradigm of this family, photoactive yellow protein (PYP) is a cytoplasmic photocycling protein related to negative phototactic response to blue light in purple photosynthetic bacteria. PYP has a p-coumaric acid chromophore binding to the cysteine residue via a thioester bond, whose vibrations were found to overlap calculated vibrations of the protein scaffold. Using our unique technique of anisotropic terahertz microscopy(ATM)[4], we measure the intramolecular vibrations for PYP for the first time, including cycling between ground and blue shift (pB) states. Room temperature ATM measurements are performed in the dark and with continuous wave illumination at 488nm, resulting in a steady pB state with approximately 5% population conversion. In pB state, we find an overall decrease in the strength of resonant band in frequency range of 30-60 cm-1. Our calculated spectra using quasi-harmonic analysis indicate that our measurements are dominated by the protein vibrations, rather than the pCA chromophore, allowing us to characterize how the scaffold dynamics changes with functional states and mutations. 1. Levantino, M., et al. Nat Commun, 2015. 6. 2. Mataga, N., et al. Chem. Phys. Lett., 2002. 352(3-4): p. 220-225. 3. Fokas, A.S., et al. Photosynth. Res., 2014. 122

Modulated orientation-sensitive terahertz spectroscopy - Singh, R.; George, D. K.; Bae, C. J.; Niessen, K. A.; Markelz, A. G. (Photonics Research, 2016)
Intramolecular vibrations of large macromolecules reside in the terahertz range. In particular, protein vibrations are closely spaced in frequency, resulting in a nearly continuous vibrational density of states. This density of vibrations interferes with the identification of specific absorption lines and their subsequent association with specific functional motions. This challenge is compounded with the absorption being dominated by the solvent and local relaxational motions. A strategy for removing the isotropic relaxational loss and isolating specific vibrations is to use aligned samples and polarization-sensitive measurements. Here, we demonstrate a technique to rapidly attain the anisotropic resonant absorbance using terahertz time domain spectroscopy and a spinning sample. The technique, modulated orientation-sensitive terahertz spectroscopy (MOSTS), has a nonzero signal only for anisotropic samples, as demonstrated by a comparison between a silicon wafer and a wire grid polarizer. For sucrose and oxalic acid molecular crystals, the MOSTS response is in agreement with modeled results for the intermolecular vibrations. Further, we demonstrate that, even in the presence of a large relaxational background, MOSTS isolates underlying vibrational resonances. (C) 2016 Chinese Laser Press
Keywords: absorption-spectroscopy; dynamics; enzyme catalysis; low-frequency modes; lysozyme; neutron-scattering; Optics; perspective; polarization modulation; proteins; water

The Role of Dynamical Transition in Protein Function: Coupling of Protein Collective Vibrations and Water Dynamics - Xu, Mengyang; Niessen, Katherine; Deng, Yanting; Michki, Nigel; Snell, Edward; Markelz, Andrea (30th Anniversary Symposium of The Protein Society, 2016)
Computational simulations have revealed protein collective vibrations prompt structural rearrangements to accomplish biological function. However, the biological importance of collective vibrations has not been experimentally demonstrated. The attempts have been hampered by the inability to distinguish localized water or side-chain relaxational motions from protein long-range vibrations using conventional techniques. The dynamical transition (DT), extensively observed using X-ray, neutron scattering, NMR and terahertz techniques [1,2], describes a rapid increase in the temperature-dependent dynamics of critically hydrated proteins above ∼220 K, and has been attributed to thermally activated solvent motions. While some proteins lose function below the specific temperature, others do not. We suggest the difference arises from the nature of the required motions for function. Specifically, functional motions enabled by long-range vibrations will be vulnerable to DT, which require surrounding solvent to be sufficiently mobile. We explored the coupling of protein vibrations to solvent dynamics by applying a recently developed technique, anisotropy terahertz microscopy [3], to directly measure the collective vibrations for lysozyme and investigate the temperature dependence in 150-300 K range. We find long-range intramolecular vibrations occur at 220K and rapidly increase in strength with increasing temperature, consistent with enhanced access above the DT. The results suggest collective vibrations are slaved to DT, and those proteins with function reliant on these motions will cease function below DT. 1. Doster,W., et al. Phys.Rev.Lett., 2010.104(9):098101. 2. Niessen,K., et al. Biophys.Rev., 2015.7,201. 3. Acbas,G., et al. Nat.Commun., 2014.5,3076.

Terahertz optical measurements of correlated motions with possible allosteric function - Niessen, Katherine A.; Xu, Mengyang; Markelz, A. G. (Biophysical Reviews, 2015)
A suggested mechanism for allosteric response is the distortion of the energy landscape with agonist binding changing the protein structure's access to functional configurations. Intramolecular vibrations are indicative of the energy landscape and may have trajectories that enable functional conformational change. Here, we discuss the development of an optical method to measure the intramolecular vibrations in proteins, namely, crystal anisotropy terahertz microscopy, and the various approaches which can be used to identify the spectral data with specific structural motions.

Terahertz Optical Measurements of Correlated Motions with Possible Allosteric Function - Niessen, K. A.; Xu, M.; Markelz, A. G. (Biophysical Journal, 2015)

Measurements and Calculations of Protein Intramolecular Vibrations in the THz Range - Niessen, K. A.; Snell, E.; Markelz, A. G. (2014 39th International Conference on Infrared, Millimeter, and Terahertz Waves, 2014)
We report the calculations and measurements of intramolecular vibrational modes and their dependence on inhibitor binding in the THz range. We see an increase in anisotropic THz absorption at low frequency with inhibitor binding in both the measurements and calculations. This surprising result suggests an increase in flexibility with binding. We will discuss the possible reasons for this discrepancy.
Keywords: charmm

Optical measurements of long-range protein vibrations - Acbas, G.; Niessen, K. A.; Snell, E. H.; Markelz, A. G. (Nature Communications, 2014)
Protein biological function depends on structural flexibility and change. From cellular communication through membrane ion channels to oxygen uptake and delivery by haemoglobin, structural changes are critical. It has been suggested that vibrations that extend through the protein play a crucial role in controlling these structural changes. While nature may utilize such long-range vibrations for optimization of biological processes, bench-top characterization of these extended structural motions for engineered biochemistry has been elusive. Here we show the first optical observation of long-range protein vibrational modes. This is achieved by orientation-sensitive terahertz near-field microscopy measurements of chicken egg white lysozyme single crystals. Underdamped modes are found to exist for frequencies >10 cm(-1). The existence of these persisting motions indicates that damping and intermode coupling are weaker than previously assumed. The methodology developed permits protein engineering based on dynamical network optimization.
Keywords: absorption; crystals; dynamics; frequency raman-spectra; hydration; lysozyme; motions; Science & Technology - Other Topics; sensitivity; simulations; spectroscopy

Probing the Stability of Fluorescent Proteins by Terahertz Spectroscopy - Xu, M. Y.; George, D. K.; Jimenez, R.; Markelz, A. G. (2014 39th International Conference on Infrared, Millimeter, and Terahertz Waves, 2014)
The higher transmission through tissues of long wavelength light motivates the development of fluorescent proteins with excitation shifted to the red. However red fluorescent proteins (RFPs) are more susceptible to photobleaching than their shorter wavelength counterparts. In particular RFPs are more susceptible to photobleaching [1]. A possible reason for this is a decrease in the structural stability of the beta barrel. Measurements of structural stability include atomic root mean squared displacement <x(2)> measured by the X-ray B-factor and neutron quasi elastic scattering. To date, X-ray measurements of RFP's do not indicate a structural stability change and systematic scattering studies have not been performed. Using THz dielectric response we examine if the picosecond structural flexibility decreases with increasing FP stability.
Keywords: dynamics

Protein Dielectric Response at Terahertz Frequencies: Correlated and Diffusive Contributions - George, D. K.; Markelz, A. G. (Terahertz Biomedical Science and Technology, 2014)

Measuring phonons in protein crystals - Acbas, G.; Niessen, K. A.; George, D. K.; Snell, E.; Markelz, A. G. (Ultrafast Phenomena and Nanophotonics Xvii, 2013)
Using Terahertz near field microscopy we find orientation dependent narrow band absorption features for lysozyme crystals. Here we discuss identification of protein collective modes associated with the observed features. Using normal mode calculations we find good agreement with several of the measured features, suggesting that the modes arise from internal molecular motions and not crystal phonons. Such internal modes have been associated with protein function.
Keywords: correlated motions; dynamics; mode; molecular crystals; molecular vibrations; normal modes; phonons; protein dynamics; spectroscopy; Terahertz

Photoactive yellow protein terahertz response: hydration, heating and intermediate states - George, Deepu K; Knab, Joseph R; He, Yunfen; Kumauchi, Masato; Birge, Robert R; Hoff, Wouter D; Markelz, Andrea G (IEEE Transactions on Terahertz Science and Technology, 2013)

Terahertz Spectroscopy of Liquids and Biomolecules - George, D. K.; Markelz, A. G. (Terahertz Spectroscopy and Imaging, 2013)

Functional State Dependence of Picosecond Protein Dynamics - Chen, J. Y.; George, D. K.; He, Y.; Knab, J. R.; Markelz, A.G. (arXiv:1105.4425, 2012)

Hydration and temperature interdependence of protein picosecond dynamics - Lipps, F.; Levy, S.; Markelz, A. G. (Physical Chemistry Chemical Physics, 2012)
We investigate the nature of the solvent motions giving rise to the rapid temperature dependence of protein picoseconds motions at 220 K, often referred to as the protein dynamical transition. The interdependence of picoseconds dynamics on hydration and temperature is examined using terahertz time domain spectroscopy to measure the complex permittivity in the 0.2-2.0 THz range for myoglobin. Both the real and imaginary parts of the permittivity over the frequency range measured have a strong temperature dependence at >0.27 h (g water per g protein), however the permittivity change is strongest for frequencies <1 THz. The temperature dependence of the real part of the permittivity is not consistent with the relaxational response of the bound water, and may reflect the low frequency protein structural vibrations slaved to the solvent excitations. The hydration necessary to observe the dynamical transition is found to be frequency dependent, with a critical hydration of 0.19 h for frequencies >1 THz, and 0.27 h for frequencies <1 THz. The data are consistent with the dynamical transition solvent fluctuations requiring only clusters of similar to 5 water molecules, whereas the enhancement of lowest frequency motions requires a fully spanning water network.
Keywords: Chemistry; dielectric-relaxation; fluctuations; inelastic neutron-scattering; lysozyme; myoglobin; percolation; Physics; spectra; spectroscopy; terahertz beams; transition; water

Improved mode assignment for molecular crystals through anisotropic terahertz spectroscopy - Singh, Rohit; George, Deepu Koshy; Benedict, Jason B; Korter, Timothy M; Markelz, Andrea G (The Journal of Physical Chemistry A, 2012)

Multi-component response in multilayer graphene revealed through terahertz and infrared magneto-spectroscopy - Ellis, C. T.; Stier, A. V.; George, D. K.; Tischler, J. G.; Glaser, E. R.; Myers-Ward, R. L.; Tedesco, J. L.; Eddy, C. R.; Gaskill, D. K.; Markelz, A. G.; Cerne, J. (37th International Conference on Infrared, Millimeter, and Terahertz Waves, 2012)

Orientation Sensitive Terahertz Resonances Observed in Protein Crystals - Acbas, G.; Snell, E.; Markelz, A. G. (2012 37th International Conference on Infrared, Millimeter, and Terahertz Waves, 2012)
A method is presented for measuring anisotropic THz response for small crystals, Crystal Anisotropy Terahertz Microscopy (CATM). Sucrose CATM measurements find the expected anisotropic phonon resonances. CATM measurements of protein crystals find the expected broadband water absorption is suppressed and strong orientation and hydration dependent resonant features.
Keywords: dynamics; mode

Terahertz / Far Infrared Spectroscopy: Protein Dynamics - Markelz, A. G. (Encyclopedia of Biophysics, 2012)

Terahertz magneto-optical polarization modulation spectroscopy - George, Deepu K; Stier, Andreas V; Ellis, Chase T; McCombe, Bruce D; Černe, John; Markelz, Andrea G (JOSA BJOSA B, 2012)

Terahertz Response and Colossal Kerr Rotation from the Surface States of the Topological Insulator Bi2Se3 - Aguilar, R. V.; Stier, A. V.; Liu, W.; Bilbro, L. S.; George, D. K.; Bansal, N.; Wu, L.; Cerne, J.; Markelz, A. G.; Oh, S.; Armitage, N. P. (Physical Review Letters, 2012)
We report the THz response of thin films of the topological insulator Bi2Se3. At low frequencies, transport is essentially thickness independent showing the dominant contribution of the surface electrons. Despite their extended exposure to ambient conditions, these surfaces exhibit robust properties including narrow, almost thickness-independent Drude peaks, and an unprecedentedly large polarization rotation of linearly polarized light reflected in an applied magnetic field. This Kerr rotation can be as large as 65 degrees and can be explained by a cyclotron resonance effect of the surface states.
Keywords: bi2te3; Physics

Terahertz spectroscopic analysis of peptides and proteins - Falconer, Robert J; Markelz, Andrea G (Journal of Infrared, Millimeter, and Terahertz Waves, 2012)

Evidence of protein collective motions on the picosecond timescale - He, Yunfen; Chen, J-Y; Knab, Joseph R; Zheng, Wenjun; Markelz, Andrea G (Biophysical Journal, 2011)

Magneto Optical Polarization Measurements using THz Polarization Modulation Spectroscopy - Stier, A. V.; George, D.; Markelz, A. G.; Cerne, J. (2011 36th International Conference on Infrared, Millimeter, and Terahertz Waves, 2011)
We report a new broad band technique for rapidly measuring the complex Faraday and Kerr rotations in materials such as topological insulators and graphene, combining the distinct advantages of THz time domain spectroscopy and polarization modulation techniques. The performance of the system is demonstrated using GaAs two dimensional electron gas in a magnetic field.

Characterization of Phonons in Molecular Crystals - Singh, R.; George, D.; Markelz, A. G. (Frontiers in Optics 2010, 2010)
We demonstrate a new technique for characterizing the phonons in molecular crystals, Modulated Orientation Sensitive Terahertz Spectroscopy (MOSTS). The technique suppresses crystal defects and solvent contributions, and enhances contributions due to molecular structure and anisotropy.

Hydration Effects on Energy Relaxation of Ferric Cytochrome C Films after Soret-Band Photoexcitation - Ye, S. J.; Markelz, A. (Journal of Physical Chemistry B, 2010)
Protein hydration plays a critical role in protein dynamics and biological processes. Pump-probe transmission measurement has been applied to investigate the hydration effects on the energy relaxation of a heme protein ferric Cytochrome c (Cyt c) film after soret-band photoexcitation. Transient dynamics study indicates that the energy internal conversion time of similar to 300 fs is independent of hydration. The vibrationally excited electronic ground-state recovery rates show two transitions at the hydration level of h = 12.4-16.5% and 21.7-23.5%. The first transition occurs at the hydration level for the onset of an increasing ferric Cyt c flexibility while the second transition occurs at the saturated hydration level. The hydration dependence of steady-state electronic absorption spectrum results shows that the Q-band peak is nearly constant in center wavelength, but the line width surprisingly narrows with increasing hydration. For the similar to 695 nm absorbance associated with the MET80-Fe bond, the intensity increases with increasing hydration and slightly blue shifts. The 695 nm peak grows rapidly at h = 12.4% and then plateaus at h = 21.7%. This research shows that similar to 695 nm absorbance and ground-state recovery rates are sensitive to the hydration of the protein. This study will aid in understanding how hydration modulates the activity of the protein dynamics at a local level.
Keywords: Chemistry; circular-dichroism; conformation change; dynamics; ferricytochrome-c; protein hydration; resolved resonance raman; spectroscopy; unfolded states; vibrational-relaxation; water-molecules

Why is THz Sensitive to Protein Functional States? Oxidation State of Cytochrome C - He,Y.; Chen, J.-Y.; Knab, J. R.; Zheng, W.; Markelz, A.G. (Terahertz Science and Technology, 2010)
We investigate the presence of structural collective motions on a picosecond time scale for the heme protein, cytochrome c, as a function of oxidation and hydration, using terahertz (THz) time-domain spectroscopy and molecular dynamics simulations. Structural collective mode frequencies have been calculated to lie in this frequency range, and the density of states can be considered a measure of flexibility. A dramatic increase in the THz response occurs with oxidation, with the largest increase for lowest hydrations and highest frequencies. For both oxidation states the measured THz response rapidly increases with hydration saturating above ~25% (g H2O/g protein), in contrast to the rapid turn-on in dynamics observed at this hydration level for other proteins. Quasi-harmonic collective vibrational modes and dipole-dipole correlation functions are calculated from the molecular dynamics trajectories. The collective mode density of states alone reproduces the measured hydration dependence providing strong evidence of the existence of these collective motions. The large oxidation dependence is reproduced only by the dipole-dipole correlation function, indicating the contrast arises from diffusive motions consistent with structural changes occurring in the vicinity of a buried internal water molecule.

The role of the protein surface on the local biological water dynamics - Liang, W.; He, Y. F.; George, D.; Markelz, A. G. (Biosensing Ii, 2009)
Protein function is reliant on structural flexibility and this flexibility is slaved to the surrounding solvent. Here we discuss how the exposed surface of the protein influences the solvent dynamics and thereby influences the protein's own structural dynamics. We discuss measurements of the THz absorption of water in the presence of hydrophilic and hydrophobic surfaces.
Keywords: alanine; dynamics; hydration; lysine; lysozyme; proteins; relaxation; spectroscopy; Terahertz; thz

The role of structure in the protein dynamical transition - He, Yunfen; Markelz, Andrea G (2008 33rd International Conference on Infrared, Millimeter and Terahertz Waves, 2008)

Terahertz dielectric sensitivity to biomolecular structure and function - Markelz, Andrea G (IEEE Journal of Selected Topics in Quantum Electronics, 2008)

Terahertz response of quantum point contacts - Song, J. W.; Kabir, N. A.; Kawano, Y.; Ishibashi, K.; Aizin, G. R.; Mourokh, L.; Reno, J. L.; Markelz, A. G.; Bird, J. P. (Applied Physics LettersApplied Physics LettersApplied Physics Letters, 2008)
We measure a clear terahertz response in the low-temperature conductance of a quantum point contact at 1.4 and 2.5 THz. We show that this photoresponse does not arise from a heating effect, but that it is instead excellently described by a classical model of terahertz-induced gate-voltage rectification. This effect is distinct from the rectification mechanisms that have been studied previously, being determined by the phase-dependent interference of the source drain and gate voltage modulations induced by the terahertz field. (C) 2008 American Institute of Physics.
Keywords: detector; devices; field-effect transistors; Physics; plasma-waves; radiation; resonant detection; subterahertz; transport

Terahertz spectroscopy of bacteriorhodopsin and rhodopsin: Similarities and differences - Balu, R.; Zhang, H.; Zukowski, E.; Chen, J. Y.; Markelz, A. G.; Gregurick, S. K. (Biophysical Journal, 2008)
We studied the low-frequency terahertz spectroscopy of two photoactive protein systems, rhodopsin and bacteriorhodopsin, as a means to characterize collective low-frequency motions in helical transmembrane proteins. From this work, we found that the nature of the vibrational motions activated by terahertz radiation is surprisingly similar between these two structurally similar proteins. Specifically, at the lowest frequencies probed, the cytoplasmic loop regions of the proteins are highly active; and at the higher terahertz frequencies studied, the extracellular loop regions of the protein systems become vibrationally activated. In the case of bacteriorhodopsin, the calculated terahertz spectra are compared with the experimental terahertz signature. This work illustrates the importance of terahertz spectroscopy to identify vibrational degrees of freedom which correlate to known conformational changes in these proteins.
Keywords: Biophysics; bovine rhodopsin; conformational-changes; elastic; frequency normal-modes; light activation; molecular-dynamics simulation; neutron-scattering; protein-coupled receptors; transmembrane helices; vibrational-modes; wild-type

Development of Tagless Biosensors for Detecting the Presence of Pathogens - Markelz, A. G.; Chen, J.-Y.; Knab, J. R.; He, Y.; Ye, S. (Terahertz Frequency Detection and Identification of Materials and Objects, 2007)

Protein dynamical transition in terahertz dielectric response - Markelz, Andrea G.; Knab, Joseph R.; Chen, Jing Yin; He, Yunfen (Chemical Physics Letters, 2007)
The 200K protein dynamical transition is observed for the first time in the terahertz dielectric response. The complex dielectric permittivity ε=ε′+iε″ is determined in the 0.2–2.0THz and 80–294K ranges. ε″ has a linear temperature dependence up to 200K then sharply increases. The low temperature linear dependence in ε″ suggests anharmonicity for temperatures 80K<t<180k, challenging="" the="" assumed="" harmonicity="" below="" 200k.="" temperature="" dependence="" is="" consistent="" with="" thermally="" activated="" sidechain="" motions="" and="" shows="" involved="" in="" dynamical="" transition="" extend="" to="" subpicosecond="" time="" scales.<="" div="">

Terahertz dielectric assay of solution phase protein binding - Chen, J. Y.; Knab, J. R.; Ye, S. J.; He, Y. F.; Markelz, A. G. (Applied Physics Letters, 2007)
The authors demonstrate a method for rapid determination of protein-ligand binding on solution phase samples using terahertz dielectric spectroscopy. Measurements were performed using terahertz time domain spectroscopy on aqueous solutions below the liquid-solid transition for water. Small ligand binding sensitivity was demonstrated using triacetylglucosamine and hen egg white lysozyme with a decrease in dielectric response with binding. The magnitude of the change increases with frequency. (c) 2007 American Institute of Physics.
Keywords: dynamics; lysozyme; Physics; spectroscopy; water

Terahertz measurements of protein relaxational dynamics - Knab, Joseph R; Chen, Jing-Yin; He, Yunfen; Markelz, Andrea G (Proceedings of the IEEE, 2007)

Hydration dependence of conformational dielectric relaxation of lysozyme - Knab, Joseph; Chen, Jing-Yin; Markelz, Andrea (Biophysical Journal, 2006)

Protein conformational dynamics measured with terahertz time domain spectroscopy - Knab, Joseph R; Chen, Jing-Yin; Ye, Shuji; He, Yunfen; Markelz, Andrea G (2006 Joint 31st International Conference on Infrared Millimeter Waves and 14th International Conference on Teraherz Electronics, 2006)

Terahertz transmission characteristics of high-mobility GaAs and InAs two-dimensional-electron-gas systems - Kabir, N. A.; Yoon, Y.; Knab, J. R.; Chen, J. Y.; Markelz, A. G.; Reno, J. L.; Sadofyev, Y.; Johnson, S.; Zhang, Y. H.; Bird, J. P. (Applied Physics Letters, 2006)
Frequency-dependent complex conductivity of high-mobility GaAs and InAs two-dimensional-electron-gas (2DEG) systems is studied by terahertz time domain spectroscopy. Determining the momentum relaxation time from a Drude model, the authors find a lower value than that from dc measurements, particularly at high frequencies/low temperatures. These deviations are consistent with the ratio tau(t)/tau(q,) where tau(q) is the full scattering time. This suggests that small-angle scattering leads to weaker heating of 2DEGs at low temperatures than expected from dc mobilit9y. (c) 2006 American Institute of Physics.
Keywords: field-effect transistors; photoconductivity; Physics; plasma-waves; radiation; resonant detection; subterahertz

Ultrafast Carriers Dynamics in GaSb/Mn Random Alloys - Ye, S.; Knab, J.; Chen, J.-Y.; Wang, S.; Cheon, M.; Luo, H.; Markelz, A. G. (Proceedings of the 28th International Conference on the Physics of Semiconductors, 2006)

Using terahertz spectroscopy as a protein binding assay - Chen, J.-Y.; Knab, J. R.; Ye, S.; He, Y.; Markelz, A. G. (Advanced Biomedical and Clinical Diagnostic Systems IV, 2006)
The vibrational modes corresponding to protein tertiary structural motion lay in the far infrared or terahertz frequency range. These collective large scale motions depend on global structure and thus will necessarily be perturbed by ligand binding events. We discuss the use of terahertz dielectric spectroscopy to measure these vibrational modes and the sensitivity of the technique to changes in protein conformation, oxidation state and environment. A challenge of applying this sensitivity as a spectroscopic assay for ligand binding is the sensitivity of the technique to both bulk water and water bound to the protein. This sensitivity can entirely obscure the signal from the protein or protein-ligand complex itself, thus necessitating sophisticated sample preparation making the technique impractical for industrial applications. We discuss methods to overcome this background and demonstrate how terahertz spectroscopy can be used to quickly assay protein binding for proteomics and pharmaceutical research.

Critical hydration and temperature effects on terahertz biomolecular sensing - Knab, Joseph; Shah, Binni; Chen, Jing-Yin; Markelz, Andrea (Chemical and Biological Standoff Detection III, 2005)

Large oxidation dependence observed in terahertz dielectric response for cytochrome c - Chen, J. Y.; Knab, J. R.; Cerne, J.; Markelz, A. G. (Physical Review E, 2005)
Far infrared dielectric response is used to characterize the collective mode density of states for cytochrome c as a function of oxidation state and hydration using terahertz time domain spectroscopy. A strong absorbance and refractive index increase was observed with the oxidation. A simple phenomenological fitting using a continuous distribution of oscillators reproduces the frequency dependence of the complex dielectric response as well as demonstrates quantitative agreement with a uniform increase in either mode density or polarizability with oxidation in the 5-80 cm(-1) frequency range. Hydration dependence measurements find that a difference in the equilibrium water content for ferri and ferro cytochrome c is not sufficient to account for the large change in terahertz response. The large dielectric increase at terahertz frequencies with oxidation suggests either a significant global softening of the potential and/or a significant increase in polarizability with oxidation.
Keywords: absorption; binding; conformation; dna; dynamics; heart ferricytochrome-c; modes; Physics; protein flexibility; spectroscopy; state

Protein dynamics studies using terahertz dielectric response - Markelz, A. G.; Knab, J. R.; Chen, J. Y. (Abstracts of Papers of the American Chemical Society, 2005)
Keywords: Chemistry

Measuring Protein Flexibility with Terahertz Spectroscopy: Basic Research and Applications - Markelz, A. G.; Chen, J.-Y.; Knab, J. R.; Maeder, M. (Proceedings of the IEEE LEOS Summer Topical Meeting, 2004)

Tagless and universal biosensor for point detection of pathogens - Markelz, Andrea G; Knab, Joseph R; Chen, Jing-Yin; Černe, John; Cox, William A (Terahertz for military and security applications Ii, 2004)

Terahertz measurements of the Photoactive Protein Bacteriorhodopsin mutant D96N: M and P states - Chen, C.-Y.; Knab, J. R.; Cerne, J.; Hillebrecht, J. R.; Birge, R. R.; Markelz, A. G. (Mater. Res. Soc. Symp., 2004)
We use terahertz (THz) spectroscopy as a biomaterials characterization tool. Previously we have shown a strong contrast between the THz dielectric response for wild type (WT) and D96N mutant of bacteriorhodopsin. In those studies we observed a large increase in the THz absorbance of WT with excitation to thermally captured photo-intermediates whereas no such increase in absorbance was observed for the mutant D96N. These results suggest that the THz response is sensitive to structural changes and relative flexibility of biomolecules. However the photo-intermediate populations of the WT and D96N samples were not equivalent in those measurements. While the WT samples had relaxed (bR), M and P state intermediates present, the D96N samples had only bR and M states. Here we present terahertz absorbance measurements of D96N as a function of M and P state populations at room temperature. The THz response is constant for intermediate states populations up to 23% M state and up to 30% P state. These results verify that there is a fundamental difference in the conformational dynamics as measured by THz dielectric response for a single residue mutation.

Thz Dielectric Response As A Function Of Protein Hydration: Intramolecular Coupling Contribution - Markelz, A. G.; Chen, J.-Y.; Knab, J. R.; Maeder, M. (Proceedings of SPIE Optics East, 2004)

Biosensing with Terahertz Spectroscopy: Ligand Binding Effects - Chen, J.-Y.; Cerne, J.; Markelz, A. G. (Proceedings of the International Symposium on Spectral Sensing Research, 2003)

Direct measurements of optical phonons in SrTiO3 nanosystems - Wolpert, D; Korolev, K; Sachs, S; Knab, J; Cox, W; Cerne, J; Markelz, A.G; Zhao, T; Ramesh, R; Moeckly, B.H (Physica E: Low-dimensional Systems and Nanostructures, 2003)
We use terahertz time domain spectroscopy to examine finite size effects on the optical phonon modes in SrTiO3 thin films. In temperature-dependent measurements we find a near absence of mode softening in the TO1 phonon frequency. Furthermore we see an increase in the soft mode frequency with reduced thickness. Both of these results correlate well with the reduced dielectric response observed for nanoscale ferroelectric systems.
Keywords: Ferroelectrics; Finite size; Mode softening; phonons; Strontium titanate; Terahertz

Finite size effects in ferroelectric nanosystems: Absence of mode softening - D. Wolpert; W. Cox; J. Cerne; A. Markelz; T. Zhao; R. Ramesh (2003 Nanotechnology Conference and Trade Show - Nanotech, 2003)
We present measurements of the mode softening behavior for PbZr 0.5Ti0.5O3 (PZT(50)) thin films using terahertz time domain spectroscopy (TTDS). The films were grown using pulsed laser deposition (PLD) techniques on silicon substrates to study how reduced size affects the mode softening behavior. At room temperature two modes are observed at 1.1 THz (37 cm-1) and at 2.3 THz (77 cm-1). As the temperature is increased toward Tc we do not see strong mode softening, but rather a spectral weight transfer from the high frequency mode to the low frequency mode. This absence of mode softening is more dramatic than that reported by other investigators[1]. We will discuss the possible sources for this discrepancy. These results suggest a change in lattice dynamics for nanoscale ferroelectric films that may be highly dependent on the sample preparation technique.
Keywords: Ferroelectric materials; Fourier Transform Infrared Spectroscopy; Frequency ranges; Lead compounds; Mode softening; nanostructured materials; Natural frequencies; Optical modes; Permittivity; phase transitions; phonons; Routers; Thermal effects

Protein flexibility and conformational state: A comparison of collective vibrational modes of wild-type and D96N bacteriorhodopsin - Whitmire, S. E.; Wolpert, D.; Markelz, A. G.; Hillebrecht, J. R.; Galan, J.; Birge, R. R. (Biophysical Journal, 2003)
Far infrared ( FIR) spectral measurements of wild-type (WT) and D96N mutant bacteriorhodopsin thin films have been carried out using terahertz time domain spectroscopy as a function of hydration, temperature, and conformational state. The results are compared to calculated spectra generated via normal mode analyses using CHARMM. We find that the FIR absorbance is slowly increasing with frequency and without strong narrow features over the range of 2-60 cm(-1) and up to a resolution of 0.17 cm(-1). The broad absorption shifts in frequency with decreasing temperature as expected with a strongly anharmonic potential and in agreement with neutron inelastic scattering results. Decreasing hydration shifts the absorption to higher frequencies, possibly resulting from decreased coupling mediated by the interior water molecules. Ground-state FIR absorbances have nearly identical frequency dependence, with the mutant having less optical density than the WT. In the M state, the FIR absorbance of the WT increases whereas there is no change for D96N. These results represent the first measurement of FIR absorbance change as a function of conformational state.
Keywords: angstrom resolution; Biophysics; dna; films; frequency; harmonic-analysis; inelastic neutron-scattering; large systems; mixed basis; normal-modes; purple membranes; structural-changes; transform infrared-spectroscopy

Terahertz Applications to Biomolecular Sensing - Markelz, A. G.; Whitmire, S. E. (International Journal of High Speed Electronics and Systems, 2003)

Terahertz applications to biomolecular sensing - Markelz, Andrea G; Whitmire, Scott E (International Journal of High Speed Electronics and Systems, 2003)

Terahertz Biosensors based on Xerogel Substrates - Chen, J.-Y.; Cox, W.; Bright, F. V.; Cerne, J.; Markelz, A. G. (Proceedings of the International Symposium on Spectral Sensing Research, 2003)

Ultrafast THz spectroscopy of photoactive biomolecules - Chen, J.-Y.; Whitmire, S. E.; Markelz, A. G.; Hillebrecht, J. R.; Birge, R. R. (Ultrafast Phenomena in Semiconductors VII, 2003)

THz time domain spectroscopy of biomolecular conformational modes - Markelz, Andrea; Whitmire, Scott; Hillebrecht, Jay; Birge, Robert (Physics in Medicine & Biology, 2002)

Terahertz Time domain spectroscopy of the M intermediate state of Bacteriorhodopsin - Whitmire, S.; Markelz, A. G.; Hillebrecht, J. R.; Birge, R. R. (Proceedings of the 26th International Conference on Infrared and Millimeter Waves, 2001)

High field pulsed terahertz measurements of nonlinear conductivity - A. G. Markelz (Nonlinear Optics: Materials, Fundamentals, and Applications, 2000)
High field pulsed terahertz spectroscopy is used to measure the inplane nonlinear conductivity response of two dimensional electron gases. Results are compared to FEL measurements suggesting LO phonon bottleneck weakening at 0.5 THz.
Keywords: 0.5 THz; 2D electron gases; Conductivity measurement; electrical conductivity measurement; Electron emission; FEL measurements; Finite impulse response filter; high field pulsed terahertz measurements; high field pulsed terahertz spectroscopy; high-speed optical techniques; inplane nonlinear conductivity response; LO phonon bottleneck weakening; nonlinear conductivity; nonlinear optics; phonons; Power measurement; Pulse measurements; Resonance; semiconductor quantum wells; spectroscopy; Submillimeter wave measurements; submillimetre wave spectroscopy; two dimensional electron gases; two-dimensional electron gas

Pulsed terahertz spectroscopy of DNA, bovine serum albumin and collagen between 0.1 and 2.0 THz - Markelz, A. G.; Roitberg, A.; Heilweil, E. J. (Chemical Physics Letters, 2000)
We report the first use of pulsed terahertz spectroscopy to examine low-frequency collective vibrational modes of biomolecules. Broadband absorption increasing with frequency was observed for lyophilized powder samples of calf thymus DNA, bovine serum albumin and collagen in the 0.06-2.00 THz (2-67 cm(-1)) frequency range, suggesting that a large number of the low-frequency collective modes for these systems are IR active. Transmission measurements at room temperature showed increasing FIR absorption with hydration and denaturing. (C) 2000 published by Elsevier Science B.V. All rights reserved.
Keywords: b-dna; Chemistry; films; modes; Physics; proteins

Relaxation times in InAs/AlSb quantum wells - Markelz, A. G.; Asmar, N. G.; Gwinn, E. G. (Applied Physics Letters, 1998)

Temperature-dependent terahertz output from semi-insulating GaAs photoconductive switches - Markelz, A. G.; Heilweil, E. J. (Applied Physics Letters, 1998)
The temperature dependence of the terahertz (THz) output power and spectra from biased photoconductive switches was measured for several antenna gap widths and applied biases. The spectrally integrated THz output had a nonmonotonic temperature dependence in all cases with the value increasing by a factor of 3 from room temperature to 150 K for low biases and 100 K at high biases. An abrupt decrease in output power occurs below 90 K, and the spectrum shifts to lower frequencies as the temperature is lowered. (C) 1998 American Institute of Physics.
Keywords: domain; generation; Physics; pulses; semiconductor surfaces; transmission spectroscopy

Interband impact ionization by terahertz illumination of InAs heterostructures - Markelz, A. G.; Asmar, N. G.; Brar, B.; Gwinn, E. G. (Applied Physics Letters, 1996)
Experimental studies of InAs heterostructures illuminated by far-infrared (FIR) radiation reveal an abrupt increase in the charge density for FIR intensities above a threshold value that rises with increasing frequency. We attribute this charge density rise to interband impact ionization in a regime in which omega tau(m) similar to 1, where tau(m) is the momentum relaxation time, and f=omega/2 pi is the FIR frequency. The dependence of the density rise on the FIR field strength supports this interpretation, and gives threshold fields of 3.7-8.9 kV/cm for the frequency range 0.3-0.66 THz. (C) 1996 American Institute of Physics.
Keywords: energy; far-infrared excitation; inas/alsb quantum-wells; inplane; modulation; Physics

Nonlinear response of quantum-confined electrons in nonparabolic subbands - Markelz, A. G.; Gwinn, E. G. (Journal of Applied Physics, 1996)
We show that quantum confinement can dramatically alter the density-dependence of the third-order susceptibility, chi(NP)((3)) that arises from band nonparabolicity. Our results predict an oscillatory dependence of the efficiencies for third-harmonic generation and four-wave mixing on the subband occupation of quantum wells, and for narrow wells with high charge densities predict an enhancement over the bulk susceptibility. We also make a simple estimate of the fields required to saturate this nonparabolicity contribution to chi((3)). We discuss these results in light of recent experiments on third-harmonic generation from narrow-gap quantum wells at frequencies of similar to 1 THz, and show that nonparabolicity may not be the only nonlinearity contributing to the large chi((3)) observed. (C) 1996 American Institute of Physics.

Temperature of quasi-two-dimensional electron gases under steady-state terahertz drive - Asmar, N. G.; Cerne, J.; Markelz, A. G.; Gwinn, E. G.; Sherwin, M. S.; Campman, K. L.; Gossard, A. C. (Applied Physics Letters, 1996)
We use photoluminescence to study the time-average energy distribution of electrons in the presence of strong steady-state drive at terahertz (THz) frequencies, in a modulation-doped 125 Angstrom AlGaAs/GaAs square well that is held at low lattice temperature TL. We find that the energy distribution can be characterized by an effective electron temperature, T-e(>T-L), that agrees well with values estimated from the THz-illuminated, dc conductivity. This agreement indicates that under strong THz drive, LO phonon scattering dominates both energy and momentum relaxation; that the carrier distribution maintains a heated, thermal form; and that phonon drift effects are negligible. (C) 1996 American Institute of Physics.
Keywords: hot-electrons; Physics

Third Harmonic Generation in a Gaas/Algaas Superlattice in the Bloch Oscillator Regime - Wanke, M. C.; Markelz, A. G.; Unterrainer, K.; Allen, S. J.; Bhatt, R. (Hot Carriers in Semiconductors, 1996)

Undressing a collective intersubband excitation in a quantum well - Craig, K.; Galdrikian, B.; Heyman, J. N.; Markelz, A. G.; Williams, J. B.; Sherwin, M. S.; Campman, K.; Hopkins, P. F.; Gossard, A. C. (Physical Review Letters, 1996)
We have experimentally measured the 1-2 intersubband absorption in a single 40 nm wide modulation-doped Al0.3Ga0.7As/GaAs square quantum well as a function of frequency, intensity, and charge density. The low-intensity depolarization-shifted absorption occurs near 80 cm(-1) (10 meV or 2.4 THz), nearly 30% higher than the intersubband spacing. At higher intensities, the absorption peak shifts to lower frequencies. Our data are in good agreement with a theory proposed by Zaluzny, which attributes the redshift to a reduction in the depolarization shift as the excited subband becomes populated.

NONLINEAR QUANTUM DYNAMICS IN SEMICONDUCTOR QUANTUM-WELLS - Sherwin, M. S.; Craig, K.; Galdrikian, B.; Heyman, J.; Markelz, A.; Campman, K.; Fafard, S.; Hopkins, P. F.; Gossard, A. (Physica D-Nonlinear Phenomena, 1995)
We discuss recent measurements of the nonlinear response of electrons in wide quantum wells driven by intense electromagnetic radiation at terahertz frequencies. The theme is the interplay of quantum mechanics, strong periodic driving, the electron-electron interaction and dissipation. We discuss harmonic generation from an asymmetric double quantum well in which the effects of dynamic screening are important. Measurements and theory are found to be in good agreement. We also discuss intensity-dependent absorption in a 400 Angstrom square quantum well. A new nonlinear quantum effect occurs, in which the frequency at which electromagnetic radiation is absorbed shifts to the red with increasing intensity. The preliminary experimental results are in agreement with a theory by Zaluzny, in which the source of the nonlinearity is the self-consistent potential in the Hartree approximation for the electron dynamics.

QUENCHING OF EXCITONIC QUANTUM-WELL PHOTOLUMINESCENCE BY INTENSE FAR-INFRARED RADIATION - FREE-CARRIER HEATING - Cerne, J.; Markelz, A. G.; Sherwin, M. S.; Allen, S. J.; Sundaram, M.; Gossard, A. C.; Vanson, P. C.; Bimberg, D. (Physical Review B, 1995)

RESONANT-ENERGY RELAXATION OF TERAHERTZ-DRIVEN 2-DIMENSIONAL ELECTRON GASES - Asmar, N. G.; Markelz, A. G.; Gwinn, E. G.; Cerne, J.; Sherwin, M. S.; Campman, K. L.; Hopkins, P. F.; Gossard, A. C. (Physical Review B, 1995)

Terahertz grid frequency doublers - Chiao, Jung-Chih; Markelz, Andrea; Li, Yongjun; Hacker, Jonathan; Crowe, Thomas; Allen, James; Rutledge, David (Proc. Sixth Intl. Symp. Space Terahertz Tech, 1995)

Third harmonic generation in a GaAs/AlGaAs Superlattice in the Bloch Oscillator Regime - Wanke, M. C.; Markelz, A.G.; Unterrainer, K.; Allen, S. J.; Bhatt, R. (Proceedings of the International Conference on Hot Carriers in Seminconductors, 1995)

DC TRANSPORT IN INTENSE, INPLANE TERAHERTZ ELECTRIC-FIELDS IN AL(X)GA(1-X)AS HETEROSTRUCTURES AT 300-K - Asmar, N. G.; Markelz, A. G.; Gwinn, E. G.; Hopkins, P. F.; Gossard, A. C. (Solid-State Electronics, 1994)
We report 300 K studies of the dependence of the in-plane, d.c. conductivity, sigma(d.c.) (E(omega)), of a quasi 2D electron gas on the amplitude E(omega) and frequency of intense, far-infrared fields (omega/2pi = 0.24-3.5 THz). We measure sigma(d.c.) (E(omega) parallel-to E(d.c.)), where E(d.c.) is a small sensing field, and observe a monotonic decrease in sigma(d.c.) with increasing E(omega). Although a simple scaling ansatz collapses the measured sigma(d.c.) (E(omega)) data onto a single curve for frequencies from 0.25-3.45 THz (at low to moderate scaled fields), the decrease in conductivity is substantially more rapid than expected from comparison to similar data taken by Masselink et al. [Solid-St. Electron. 31, 337 (1988)] at 35 GHz. We tentatively attribute this difference to effects of a high-frequency modulation in the electron temperature.

ENERGY RELAXATION AT THZ FREQUENCIES IN ALXGA1-XAS HETEROSTRUCTURES - Asmar, N. G.; Markelz, A. G.; Gwinn, E. G.; Hopkins, P. F.; Gossard, A. C. (Semiconductor Science and Technology, 1994)
We report 4.2 K studies of the dependence of the in-plane, DC conductivity of a quasi 2D electron gas on the amplitude E(omega) of applied fields with frequencies from 0.25 THz to 3.5 THz. We analyse the dependence of sigma(DC) on E(omega) assuming that electron-optical phonon scattering dominates energy relaxation, that the absorbed power has a Drude form and that the electron distribution is thermal. This simple analysis is self-consistent: Arrhenius plots of the estimated energy loss rate have a slope near -homega(LO)BAR/k(B) for all frequencies, as expected for energy loss by optical phonon emission. We find that the effective energy relaxation time tau(epsilon) varies with the frequency of the applied field, from tau(epsilon) approximately 4 ps at 0.34 THz to tau(epsilon) approximately 0.3 ps at 3.45 THz. This may indicate a frequency-dependent form for the hot-phonon distribution.

Far-infrared harmonic generation from semiconductor heterostructures - Markelz, A.G.; Gwinn, E. G.; Sherwin, M. S.; Heyman, J. N.; Nguyen, C.; Kroemer, H. (SPIE Proceedings, 1994)

FAR-INFRARED SATURATION SPECTROSCOPY OF A SINGLE SQUARE-WELL - Craig, K.; Felix, C. L.; Heyman, J. N.; Markelz, A. G.; Sherwin, M. S.; Campman, K. L.; Hopkins, P. F.; Gossard, A. C. (Semiconductor Science and Technology, 1994)
We have performed saturation spectroscopy measurements of the lowest intersubband transition in a single 400 angstrom GaAs/Al0.3Ga0.7As modulation-doped square quantum well. We couple intense tunable far-infrared radiation from the Santa Barbara free electron laser into our sample using an edge-coupling technique and measure absorption as a function of frequency and intensity. Saturation and frequency shifts in the absorption line are clearly observed. We attribute the frequency shifts to reductions in the many-body depolarization shift. From our preliminary measurements, we estimate the intersubband relaxation time to be 600 ps to within a factor of three.

Frequency Dependence of the Third Order Susceptibility of InAs Quantum Wells at Terahertz Frequencies - Markelz, A.G.; Cerne, J.; Gwinn, E. G.; Brar, B.; Kroemer, H. (Proceedings of the International Conference on the Physics of Semiconductors, 1994)

GIANT 3RD-ORDER NONLINEAR SUSCEPTIBILITIES FOR INPLANE FAR-INFRARED EXCITATION OF SINGLE INAS QUANTUM-WELLS - Markelz, A. G.; Gwinn, E. G.; Sherwin, M. S.; Nguyen, C.; Kroemer, H. (Solid-State Electronics, 1994)
Third-order, free-carrier nonlinear susceptibilities, chi(3), have been measured between 19 and 23 cm-1 for three InAs/AlSb quantum wells with sheet densities between 2.5 x 10(12) cm-2 and 8 x 10(12) cm-2. We find that these wells are strongly nonlinear at far-infrared frequencies: odd harmonics ninth order have been observed at high incident intensities, and the peak value of chi(3) reaches approximately 1 esu. This is several orders of magnitude larger than previously reported values for chi(3) in bulk n-GaAs (10(-4) esu)[1] and in polyacetylene (10(-7) esu)[2]. The large magnitude of chi(3) is attributed to the high carrier density in the InAs wells, and to the strong non-parabolicity of the conduction band in InAs. However, the free-carrier chi(3) for bulk InAs predicts a density-dependence different from that observed, and the measured decrease in chi(3) with increasing intensity indicates non-perturbative response. We find that the anisotropy of chi(3) displays the expected 4-fold symmetry.

PROBING TERAHERTZ DYNAMICS IN SEMICONDUCTOR NANOSTRUCTURES WITH UCSB FREE-ELECTRON LASERS - Allen, S. J.; Craig, K.; Felix, C. L.; Guimaraes, P.; Heyman, J. N.; Kaminski, J. P.; Keay, B. J.; Markelz, A. G.; Ramian, G.; Scott, J. S.; Sherwin, M. S.; Campman, K. L.; et al. (Journal of Luminescence, 1994)
The UCSB free-electron lasers provide kilowatts of continuously tunable radiation from 120 GHz to 4.8 THz. They have the most impact on terahertz science and technology that require a tunable, high power source to explore non-linear dynamics or that sacrifice incident power to recover the linear response of systems with very small cross-section. We describe three experiments that demonstrate the utility of these lasers in experiments on the terahertz dynamics of semiconductor nanostructures: (i) terahertz dynamics of resonant tunneling diodes, (ii) saturation spectroscopy of quantum wells and (iii) photon-assisted tunneling in superlattices.

SUBCUBIC POWER DEPENDENCE OF 3RD-HARMONIC GENERATION FOR INPLANE, FAR-INFRARED EXCITATION OF INAS QUANTUM-WELLS - Markelz, A. G.; Asmar, N. G.; Gwinn, E. G.; Sherwin, M. S.; Nguyen, C.; Kroemer, H. (Semiconductor Science and Technology, 1994)
Large third-order, free-carrier nonlinear susceptibilities, chi(3) (to approximately 0.2 esu), and subcubic dependence of the third-harmonic power on the incident intensity, have been observed between 19 cm-1 and 23 cm-1 for InAs/AlSb quantum wells with electron sheet densities between 2.5 x 10(12) cm-2 and 8 X 10(12) cm-2. We find that the transmission of the fundamental, and the samples' DC conductivity, decrease with increasing incident intensity, indicating a large rise in the scattering rate. Using the intensity-dependent transmission to account for absorption in the sample is not sufficient to recover a cubic power law for the third-harmonic intensity. In addition, given the increased scattering rate indicated by the conductivity data, the bulk free-carrier chi(3) due to non-parabolicity should decrease dramatically with increasing fundamental intensity, contrary to our results. Thus, non-parabolicity alone cannot account for the observed third-harmonic response.

Far-infrared nonlinear response of electrons in semiconductor nanostructures - Sherwin, M. S.; Asmar, N. G.; Bewley, W. W.; Craig, K.; Felix, C. L.; Galdrikian, B.; Gwinn, E. G.; Markelz, A.G.; Gossard, A. C.; Hopkins, P. F.; Sundaram, M.; Birnir, B. (SPIE Proceedings, 1993)

Site-selective oxygen-isotope substitution in YBa2Cu3O7−δ - Morris, D. E.; Markelz, A. G.; Wei, J. Y. T.; Huitgren, C. T.; Nickel, J. H.; Hamilton, J. C.; McCarty, K. F. (Physical Review B, 1991)
We report selective substitution of oxygen-18 and oxygen-16 isotopes into the inequivalent oxygen lattice sites in YBa2Cu3O7−δ. The technique involves gas-phase diffusion and exploits the site dependence of diffusion rates. The CuO2-plane [O(2),O(3)] sites of YBa2Cu3O7−δ can be filled with 18O while the apical [O(4)] and CuO-chain sites [O(1)] contain 16O (the opposite distribution can also be made). The site-selective isotope occupation has been confirmed by Raman spectroscopy. Our method will permit experiments to determine the contributions of the different oxygen sites to the isotope effect, in order to locate the pairing interaction within the unit cell.

Conversion of 124 and 123 + cupric oxide: microstructure and phase diagram - Morris, D. E.; Nickel, J. H.; Markelz, A.G.; Gronksy, R.; Fendorf, M.; Burmester, C. P. (Materials Research Society Symposium Proceedings, 1990)

CONVERSION OF 124 INTO 123+CUO AND 124, 123 AND 247 PHASE REGIONS IN THE Y-BA-CU-O SYSTEM - Morris, D. E.; Markelz, A. G.; Fayn, B.; Nickel, J. H. (Physica C, 1990)

8 NEW HIGH-TEMPERATURE SUPERCONDUCTORS WITH THE 1-2-4 STRUCTURE - Morris, D. E.; Nickel, J. H.; Wei, J. Y. T.; Asmar, N. G.; Scott, J. S.; Scheven, U. M.; Hultgren, C. T.; Markelz, A. G.; Post, J. E.; Heaney, P. J.; Veblen, D. R.; Hazen, R. M. (Physical Review B, 1989)

OXYGEN CONCENTRATION EFFECT ON TC OF THE BI-CA-SR-CU-O SUPERCONDUCTOR - Morris, D. E.; Hultgren, C. T.; Markelz, A. M.; Wei, J. Y. T.; Asmar, N. G.; Nickel, J. H. (Physical Review B, 1989)

SMALL OXYGEN ISOTOPE SHIFT IN YBA2CU3O7 - Morris, D. E.; Kuroda, R. M.; Markelz, A. G.; Nickel, J. H.; Wei, J. Y. T. (Physical Review B, 1988)

SPECIFIC-HEAT MEASUREMENTS ON SUPERCONDUCTING BI-CA-SR-CU AND TL-CA-BA-CU OXIDES - ABSENCE OF A LINEAR TERM IN THE SPECIFIC-HEAT OF BI-CA-SR-CU OXIDES - Fisher, R. A.; Kim, S.; Lacy, S. E.; Phillips, N. E.; Morris, D. E.; Markelz, A. G.; Wei, J. Y. T.; Ginley, D. S. (Physical Review B, 1988)